Amino acid 15N analysis reveals change in the importance of freshwater resources between the hunter‐gatherer and farmer in the Neolithic upper Tigris. Issue 4 (28th January 2019) - Itahashi, Yu; Erdal, Yilmaz Selim; Tekin, Halil; Omar, Lubna; Miyake, Yutaka; Chikaraishi, Yoshito; Ohkouchi, Naohiko; Yoneda, Minoru
Abstract: Objective: The inhabitants of several sites in the Upper Tigris Valley, such as Hakemi Use, domesticated animals and cereals during the Pottery Neolithic period, while the inhabitants in this valley were hunter–gatherers in the Pre‐Pottery Neolithic period, consuming freshwater and terrestrial food resources. However, there is considerable uncertainty surrounding whether or not changes in dietary food composition accompanied the shift in food production away from foraging. In order to reveal the impact of the development of agriculture on the human diet over the Pre‐Pottery and Pottery Neolithic periods in this region, we analyzed the isotopic compositions of amino acids from the farmers at the Hakemi Use Pottery Neolithic site, and compared them with those from the Pre‐Pottery hunter–gatherers in the close region. Materials and Methods: Herein, we report the nitrogen isotopic compositions of amino acids, as well as both carbon and nitrogen isotopic compositions of bulk collagen, from human and faunal remains collected from Hakemi Use. Results: Whereas freshwater resources were consumed by hunter–gatherers in this region during the Pre‐Pottery period, the δ 15 N values of glutamic acid (δ 15 NGlu ) and phenylalanine (δ 15 NPhe ) suggest that freshwater food resources were rarely consumed by inhabitants following the development of agriculture. Discussion: Despite living in similar settings by the Tigris as its inhabitants during the Pre‐Pottery period, the farmers of the Pottery Neolithic period depended less on freshwater resources for their diets relative to the hunter–gatherers of the Pre‐Pottery Neolithic period.